Pengaruh Kinerja Pelayanan Dan Facilitating Condition Terhadap Kepuasan Masyarakat Pengguna Operator Penerbitan KTP Elektronik (KTP-EL) Di Kota Padang - Sri Ratna; Lidya Martha (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine and analyze the effect of service performance and facilitating conditions on community satisfaction using Electronic KTP issuance operators (KTP-EI) in Padang City. This type of research is quantitative research. This study used primary data obtained through distributing questionnaires to people who received KTP-El services at the Padang City Population and Civil Registration Service. Sampling in this study using random sampling technique. The number of samples in this study were 200 respondents. The data analysis technique used is multiple linear regression and statistical t-test. The results of the study show that service performance and facilitating conditions have a positive and significant effect on community satisfaction using Electronic KTP issuance operators (KTP-EI) in Padang City. Community satisfaction is influenced by service performance and facilitating condition variables by 93.80% while the remaining 6.20% is influenced by other factors not examined in this study.